Penerapan Algoritma Genetika Untuk Optimasi Penjadwalan pada MTS Negeri 1 Pangkalpinang - Delpiah Wahyuningsih; Ellya Helmud (ISB Atma Luhur, 2020)
Scheduling is a very important thing to do at school. The schedule, which is still being carried out manually at MTS Negeri 1 Pangkalpinang, requires time to manage teacher slots, classes, subjects, and times where in MTS teacher hours have been determined by the department of religion so that it takes quite a long time to process the formation of the schedule. This study aims to utilize genetic algorithms in optimizing scheduling in a short time. The genetic algorithm is an algorithm that is effective in dealing with scheduling. The results of data testing were carried out with 15, 20, 25 and 30 subjects. Testing with 15 subjects took 19.56 seconds to form a schedule and there were no conflicting schedules, while with 20 data subjects the time to process the schedule formation took 42.15 seconds, 25 data with 94.07 seconds and 30 data with time 471.60. The average time required to process the data is 156.845 seconds.